Evaluation of Babesia gibsoni GPI-anchored Protein 47 (BgGPI47-WH) as a Potential Diagnostic Antigen by Enzyme-Linked Immunosorbent Assay - Zhan, Xueyan; Yu, Long; An, Xiaomeng; Liu, Qin; Li, Muxiao; Nie, Zheng; Zhao, Yangnan; Wang, Sen; Ao, Yangsiqi; Tian, Yu; He, Lan; Zhao, Junlong (Frontiers in Veterinary Science, 2019)
Babesia gibsoni is one of the important pathogens causing severe incurable canine babesiosis, suggesting the necessity to develop a sensitive, specific, and highly automated diagnostic method for clinical application. Surface proteins are ideal candidates for diagnostic targets because they are the primary targets for host immune responses during host-parasite interactions. Glycosylphosphatidylinositol (GPI)-anchored proteins are abundant on the surface of parasites and play an important role in parasite diagnosis. In this study, a GPI-anchored protein named BgGPI47-WH was obtained and mouse anti-rBgGPI47-WH polyclonal antibody was produced by immunizing mice with the purified protein and Freund's adjuvant. Western blot was used to identify the native form and immunogenicity of BgGPI47-WH. An ELISA method was established by using recombinant BgGPI47-WH protein to evaluate its potential as a diagnostic antigen and the established method exhibited high specificity. The antibody response was evaluated by using the B. gibsoni-infected sera collected from different experimental dogs and the established ELISA could recognize antibodies at day 6 until day 101 post infection, indicating the potential use of BgGPI47-WH for early stage diagnosis. The specificity of the established ELISA was further evaluated by using 147 clinical samples collected from animal hospitals and 17.0% (25/147) of the samples were tested positive, with an overall proportion agreement of 86.39% between the results from BgGPI47-WH and BgSA1. Our results indicated that BgGPI47-WH could be used as a reliable diagnostic antigen and this study has proposed a practical method for early diagnosis of B. gibsoni.